Predictors and Moderator of Telework Adjustment among Labour Union Members During Covid-19 Pandemic: A Conceptual Paper - Azizan H Morshidi; Kee Y. Sabariah Kee Mohd Yussof; Jalihah Md. Shah (Human Resource Management Academic Research Society (HRMARS), 2021)
The pandemic catastrophe caused by covid-19 poses unprecedented problems and has far-reaching ramifications for how people working life. Digital technologies have been critical in preserving corporate continuity since lockdown tactics drove employees worldwide to telework, frequently leaving them ill-equipped and unprepared. Thus, labour union members as active employees have been forced to adapt to changing work conditions and practices, as articulated in the Theory of Work Adjustment (TWA). This article suggests that gender may be used to moderate the impacts of trade union support and professional isolation on labour union members telework adjustment during the COVID-19 pandemic. This conceptual paper posits that telework adjustment may be researched by utilising a local union sample. Additionally, this article serves as a conceptual framework for future study by drawing on theoretical and empirical findings from essential works in adjacent domains.